"Castaway Categories": Examining the Re-Emergence of the "Underclass" in the UK. Issue 1 (2nd January 2019) - Garrett, Paul Michael
ABSTRACT: Throughout the 1980s and early 1990s, discussion of poverty often incorporated references to a so-called underclass and its purported welfare dependency. This largely disparaging keyword now seems to have reappeared; recent uncritical references have been seeping into social work's academic literature. Dwelling primarily on the United Kingdom, this article reveals that the "underclass" notion seems to have been reignited around the time of the economic crisis that began in 2007. This coincided with public concerns about child-protection services. It was, however, the English riots (August 6 to 11, 2011) that multiplied the use of the appellation underclass in media and political discourses. However, disparaging designations of those who are unemployed or low-waged have been present across centuries; the troubled family is the most recent construction. In this context, Loïc Wacquant furnishes a useful analytical framework to conceptualise how underclass stereotypes and other castaway categories are described, contained, and managed.